2008
DOI: 10.1017/s006824540000006x
|View full text |Cite
|
Sign up to set email alerts
|

Neolithic Lime Plastered Floors in Drakaina Cave, Kephalonia Island, Western Greece: Evidence of the Significance of the Site

Abstract: The Neolithic layers of Drakaina Cave in Kefalonia Island are characterized by several successive well-preserved plaster floors. These constructed floors, along with the relating archaeological sediments, were examined using micromorphological techniques, which involve the study of petrographie thin sections produced by resin-impregnated, undisturbed blocks of sediment.At Drakaina, lime plaster was identified as the construction material of the floors, which consist of a mixture of clay and burnt lime as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Matthews () and Shahack‐Gross () explain the formation of phosphatic features and nodules in association with archaeological floors by decomposition of organic materials related to food preparation or derived from either waste or dung‐based materials. Karkanas and Stratouli () report apatite formation on a calcareous floor within a cave suggesting that apatite formed from human activities such as animal processing. It is therefore suggested that thin phosphatic coatings on the floor gravels at the EWT may have precipitated out of phosphate‐bearing solutes originating from anthropogenic waste materials in the floor context.…”
Section: Discussionmentioning
confidence: 99%
“…Matthews () and Shahack‐Gross () explain the formation of phosphatic features and nodules in association with archaeological floors by decomposition of organic materials related to food preparation or derived from either waste or dung‐based materials. Karkanas and Stratouli () report apatite formation on a calcareous floor within a cave suggesting that apatite formed from human activities such as animal processing. It is therefore suggested that thin phosphatic coatings on the floor gravels at the EWT may have precipitated out of phosphate‐bearing solutes originating from anthropogenic waste materials in the floor context.…”
Section: Discussionmentioning
confidence: 99%
“…Authigenic apatite can replace calcitic ash and calcareous shells, and it can alter limestone to the point where it is no longer recognizable. Phosphate-rich solutions from the degradation of food products have also been reported to alter lime floors and form apatite alteration surfaces (Figure 3) (Karkanas and Stratouli, 2008;Regev et al, 2010). In the case of ash, the general structure of the burnt layer, i.e., ashes overlying an organic/charcoal-rich or fire-reddened substrate, can still be recognized after alteration to apatite.…”
Section: Authigenesis and Cementationmentioning
confidence: 99%
“…The neolithic deposits of Drakaina, which measure up to 1,50-1,70 m in thickness, are marked by the presence of several successive lime 'floors' (fig. 5), constructed at intervals over a time span of almost a millennium (Karkanas 2002;Karkanas and Stratouli 2008).…”
Section: Drakaina Cave: Setting -Chronology -Neolithic Findingsmentioning
confidence: 99%
“…Furthermore, the occupational deposits of Neolithic Drakaina comprise in situ preserved remains of hearths, lined by stones from the cave environment and millstones in secondary use, as well as material of several raked-out fire installations mixed with burnt food remains (Karkanas and Stratouli 2008).…”
Section: Drakaina Cave: Setting -Chronology -Neolithic Findingsmentioning
confidence: 99%